In the given figure, if AC = BD the prove that AB = CD
Attachments:
![](https://hi-static.z-dn.net/files/d39/51d35b21edec19d0180dfd0c330cce93.jpg)
Answers
Answered by
11
Answer:
AC = BD
AB + BC = BC + CD
AB = BC + CD - BC
AB = CD
Answered by
2
Answer:
to prove : AB = CD
given : AC = BD
proof :
we have to prove that AB = CD. So, we have to somehow relate this to the given relation AC = BD.
from the figure, we can say that
AB = AC-BC and CD = BD-BC
and we know that, AC = BD
then, AC-BC = BD-BC
i.e, AB = CD.
hence, proved.
Similar questions